Locating August Strindberg's prose : modernism, transnationalism, and setting - Stenport, Anna Westerståhl (University of Toronto Press, 2010)
"The setting of a novel is more than just an anonymous, interchangeable backdrop. In Locating August Strindberg's Prose, Anna Westerstahl Stenport argues that spatial setting is a key - though often neglected - tool for exploring the fundamentals of European literary modernism